Lymphocytic Host Response and other Prognostic Factors in Early Stage Squamous Cell Carcinoma of Tongue: Retrospective Analysis from a Tertiary Cancer Center - Nagarajan, Aswin Anapathoor; Rajaraman, Swaminathan; Sundersingh, Shirley; Thangarajan, Rajkumar (South Asian Journal of Cancer, 2023)
Introduction The tongue is the most common site of malignancy in the oral cavity, and squamous cell carcinoma is the commonest histology. The prognosis remains unfavorable despite treatment, resulting in higher mortality rates. Early stage carcinoma of the tongue is a distinct entity and is primarily treated with either surgery or radiotherapy. Various factors have been implicated in the prognosis of early stage tongue carcinomas. The main objective of this study is to access whether the lymphocytic host response (LHR) and other prognostic factors influence the survival.Patients and Methods The data of 129 patients with Stage I and Stage II (T1-2, N0) tongue cancer treated in our institute from January 2012 to December 2016 were retrospectively abstracted from the hospital case records. The various clinical and pathological factors were recorded. The Kaplan–Meier model was used for survival analysis. The disease-free survival (DFS) and the overall survival (OS) with respect to stage and LHR were calculated.Results On multivariate analysis, site of lesion, comorbidities, habits, grade of the tumor, perineural infiltration (PNI) did not influence the survival. The main factor which was found to be significant in DFS was LHR. The DFS was better for the patients who had lymphocytic infiltration of ≥ 70% (strong LHR) when compared with <70%(weak LHR) (p = 0.037). The OS with respect to stage (p = 0.608) and LHR (p = 0.164) was not found to be statistically significant.Conclusion The patients with weak LHR had less DFS when compared with patients with strong LHR. Larger studies are needed to evaluate whether adding adjuvant therapy may benefit the patients with weak LHR in early stage tongue cancer.
Keywords: squamous cell carcinoma; lymphocytic host response; Kaplan–Meier model; disease-free survival (DFS); overall survival (OS)